BRANDING OF THE TRADITIONAL VILLAGE OF DESA KOTO SENTAJO KUANTAN SINGINGI REGENCY - Arindo Karisma; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Koto Sentajo Tourism Village is one of the villages in Sentajo Raya District. Koto Sentajo Village is located between Muaro Sentajo Village and Sentajo New Village, Sentajo Raya District. Koto Sentajo Village is a village known for having tourism potential in terms of cultural heritage. Koto Sentajo Village Traditional Village is a traditional area for all communities in Sentajo Raya Kenegerian. This traditional village is one of the icons of Sentajo Raya District located in Koto Sentajo Village. This study aims to find out what the meaning of Koto Sentajo Village Traditional Village as Tourism Village Branding and find out how to Promote Koto Sentajo Village as a Customary Area. The data collection techniques used in this study are case studies, observations, interviews and documentation. The result of this research is that the Koto Sentajo Village Traditional Village can be the branding of the Koto Sentajo Tourism Village. The Traditional Village of Koto Sentajo Tourism Village uses the Kuantan Singingi Regency Brand. The promotion carried out by the government and the people is already quite good. Keywords: Traditional Village, Tourism Village, Branding, Promotion